An oral lipidic native testosterone formulation that is absorbed independent of food. Issue 5 (5th October 2021) - Newell-Price, John; Huatan, Hiep; Quirke, Jo; Porter, John; Daniel, Eleni; Mumdzic, Enis; Voet, Bernard; Keevil, Brian; Whitaker, Martin J; Ross, Richard J
Abstract : Context: There is no licensed oral native testosterone (NT) because of challenges in the formulation. Licensed oral formulations of the ester, testosterone undecanoate (TU), require a meal for absorption and generate supraphysiological dihydrotestosterone (DHT) levels. Objective: To develop an oral NT formulation. Design and methods: A lipid-based formulation of native testosterone filled into soft-gelatin capsules at 40 mg per capsule was designed with 2 years of stability at ambient temperature. Pharmacokinetic comparison studies of this oral lipidic NT formulation to oral TU were conducted in dogs and hypogonadal men. Results: In dogs, 40 mg NT was well absorbed under fasted conditions whereas 40 mg TU required a high-fat meal: for NT, the mean fed/fasted AUC ratio was 1.63 and for TU 7.05. In hypogonadal men, fed and fasted NT had similar pharmacokinetics: Cmax mean 26.5 vs 30.4 nmol/L (769 vs 882 ng/dL), AUC0–10 h 87 vs 88.6 h nmol/L. NT (fed state) showed a testosterone AUC increase of 45% between 120 and 200 mg, and NT 200 mg gave a similar mean AUC0–10 h to TU 80 mg: 87 vs 64.8 h nmol/L. Serum TU levels were variable and on a molar basis were ten-fold higher than serum testosterone levels after TU 80 mg fed. The DHT: testosterone AUC0–10 h ratio was more physiological for NT than TU being 0.19 vs 0.36. There were no emerging safety concerns with NT. Conclusion: This novel oral lipidic native testosterone formulation has potential advantages over oral TU of dosing independently of food and a lower risk of supraphysiological DHT levels. Significance statement There is no licensed oral testosterone because of challenges in formulation, and the oral formulations of the ester, testosterone undecanoate, require a fatty meal for absorption and generate supraphysiological dihydrotestosterone levels. We have overcome the design challenges and formulated an oral native testosterone that can be taken with or without food and provides physiological levels of testosterone and dihydrotestosterone in hypogonadal men. This formulation, DITEST, has the potential advantage of being oral for patients who do not tolerate injections and less risk of adverse events that might theoretically be associated with elevated dihydrotestosterone levels. Future studies will need to define the dosing regimen for replacement in hypogonadal men.